1996
DOI: 10.1111/j.1600-0420.1996.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of nasal mucosa after severe chemical and thermal eye burns

Abstract: Between February 1992 and March 1994, reconstruction of the fornices in 17 patients with extensive symblephara or lid fusion after most severe eye burns was performed with nasal mucosa from the inferior conchae as graft material. The time between accident and transplantation ranged from 2-64 months. All patients were followed for 6 to 31 months. Reconstruction of the fornices was achieved in 13 patients. Postoperative Schirmer-tests revealed markedly improved results. Impression cytology showed a persistence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
1
15
0
2
Order By: Relevance
“…In our study, the mean age was in accordance with the above data. In previous studies, it has been shown that the ocular chemical burns occur usually between 20-40 years of age [19]. Our study was compatible with the literature with regard to gender and age distribution.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the mean age was in accordance with the above data. In previous studies, it has been shown that the ocular chemical burns occur usually between 20-40 years of age [19]. Our study was compatible with the literature with regard to gender and age distribution.…”
Section: Discussionsupporting
confidence: 82%
“…To cover the conjunctival defect, a number of tissues have been used before. [3][4][5][6][7][8][9] Although a conjunctival autograft may be used to cover a small defect, in most of these patients the defect was large and there was no sufficient residual conjunctiva. Furthermore, although autologous nasal mucosa has been used successfully for fornix reconstruction, 7,8 the technique for harvesting nasal mucosa is complex and challenging.…”
Section: Discussionmentioning
confidence: 99%
“…To cover the tarsal and/or bulbar conjunctival defects, a number of tissues have previously been used, including conjunctival graft, amniotic membrane, oral mucosa, nasal mucosa, and splitthickness skin graft. [3][4][5][6][7][8][9][10] Furthermore, adjunctive measures may also be used to further prevent the reformation of adhesion; these may include intraoperative mitomycin C (MMC) application, 11 symblepharon ring, 12 or postoperative application of beta irradiation. 13 However, it remains mostly unknown which surgical technique has the optimal results for eyes with severe symblepharon.…”
mentioning
confidence: 99%
“…They predominantly occur in young male subjects and are associated with industrial accidents, domestic use of alkali, and criminal assault. [57][58][59] The incidence may have reduced in developed countries as a result of Health and Safety legislation regarding the use of protective eyewear. However, despite recent advances, ocular surface reconstruction of the severely affected eye will continue to present a challenge.…”
Section: Discussionmentioning
confidence: 99%